Optimizing multiplex PCR for drug metabolizing enzyme (CYP2C9) by adding adjuvants / Nur Hidayah Ismail - Ismail, Nur Hidayah (2006)
Adjuvants are chemicals that are used in PCR to enhance the amplification reaction .Many adjuvants have been proved to produce PCR assays which are very sensitive and specific. In this study, we used several chemicals as adjuvants in enhancing amplification of DNA replication with high GC content. Five different types of adjuvants were chosen in this experiment. The concentration of the adjuvants was optimized for the amplification of a drug metabolizing enzyme, CYP2C9. An established PCR assays for detection of polymorphism CYP2C9 was tested by using the adjuvants chosen. The test was then optimized by varying the concentration of the adjuvants as well as PCR condition. The aim of this study is to illustrate the suitable adjuvants and the range of concentration which are possible to optimize PCR for CYP2C9. The possible effective concentration of adjuvants which can optimize PCR was searched from journal and also website. Then, working solution for all adjuvants were prepared according to their effective concentration. RLKWL 001 and Bovine Serum Albumin were found to be the best adjuvants that enhance the specificity of currently available method. However, RLKWL 002, betaine and Dimethyl sulfoxide (DMSO) did not show significant improvement. The PCR assay with adjuvants were requiring further more testing with a larger sample size to determine its sensitivity and specificity.